A notification system model for bioinformatics community of practice - Abdullah, Rusli; Mohd Nor, Norhashimi; Mohamed Talib, Amir (Canadian Center of Science and Education, 2010)
Bioinformatics can be considered as a new field of study and it promises a vast exploration area (Carzaniga., Rosenblum., Wolf ., 2001). In order to expedite the maturity in this area, a proper and supportive portal where all researchers could gather and cooperate in conducting their research need to be established. One of the features in a portal that can assist Bioinformatics researchers in performing their work is the ability of the portal to notify. Notification system is a combination of software and hardware to provide a method of distributing message(s) to a set of recipients. The notification messages could assist the recipients in many ways, from time saving and cost saving till life saving. Notification system can be developed with numerous functions depending on the needs and one of the most beneficial functions in research area is notification on the next most relevant knowledge to be read. This type of notification could lessen the researchers’ time in finding the correct thus enhancing their research efficiency. Another type of notification that could assist researchers is the events reminder. Busy and hectic researchers could forget their pack schedule and put total focus on their research while the reminder prompts them when it is time through Windows’ pop up, email and SMS as the means of delivering the messages. Whilst the knowledge management system (KMS) provides a sturdy basic for the Bioinformatics portal as a whole, the agent technology support the operation of the notification system. Agent technology offers great capabilities in ensuring the recipients is notified accordingly through its autonomous, learning and cooperative characteristics. The objective of this project is to build a notification system for Bioinformatics community of practice (CoP). Researchers in this community could utilize this system to make their research process more efficient.